PENGAWASAN PROGRAM KUR PADA KANCA BRI UNIT AHMAD YANI KOTA MAKASSAR - Ariani Ariani; Muhammad Idris; Alimuddin Said (Kolaborasi : Jurnal Administrasi Publik, 2018)
The object of research was to find out the of supervision of credit program in Makassar city at branch office of Bri unit Ahmad Yani. This research is a describe the shape of wualitative service the form internal supervision. This type of research is a case study. The collection of the data used interview, observation and documentation. While techiques to analuze the data used data reduction, data presentation and conclusion. Validity of the data used triangulation of time, resources and techniques. The results showed that the of suerviing credit business Kur program in Makassar city Bri unit of Ahmad Yani unit based on internal control indicator that has been determined by audit bri that is 1) internal audit,2)review, the next is the internal supervision at bri is not good, seen in the of supervision daeler kur Keywords : Implementation of supervision, Service Kur